Sleeping position, oxygen saturation and lung volume in convalescent, prematurely born infants. Issue 5 (29th September 2006) - Kassim, Zainab; Donaldson, Nora; Khetriwal, Babita; Rao, Harish; Sylvester, Karl; Rafferty, Gerrard F; Hannam, Simon; Greenough, Anne
Abstract : Objective: To determine whether the effects of sleeping position on lung volume and oxygenation are influenced by postmenstrual age (PMA) and oxygen dependency in convalescent prematurely born infants. Design: Prospective study. Setting: Tertiary neonatal unit. Patients: 41 infants (21 oxygen dependent), median gestational age 28 weeks (range 24–31 weeks) and birth weight 1120 g (range 556–1780 g). Intervention: Infants were studied both supine and prone at two-weekly intervals from 32 weeks' PMA until discharge. Each posture was maintained for 1 h. Main outcome measures: Pulse oximeter oxygen saturation (Spo 2 ) was monitored continuously, and at the end of each hourly period functional residual capacity (FRC) was measured. Results: Overall, lung volumes were higher in the prone position throughout the study period; there was no significant effect of PMA on lung volumes. Overall, Spo 2 was higher in the prone position (p = 0.02), and the effect was significant in the oxygen-dependent infants (p = 0.03) (mean difference in Spo 2 between prone and supine was 1.02%, 95% CI 0.11% to 1.92%), but not in the non-oxygen-dependent infants. There was no significant influence of PMA on Spo 2 . Conclusion: In the present study, prone sleeping did not improve oxygenation in prematurely born infants, 32 weeks' PMA or older and with no ongoing respiratory problems. However, the infants were monitored in each position for an hour, thus it is recommended that oxygen saturation should continue to be monitored after 32 weeks' PMA to be certain that longer periods of supine sleeping are not associated with loss of lung volume and hypoxaemia.